A clinical study: Evaluation of the slimming and hypoglycemic potential of medicinal plants Equisetum arvense and Camellia sinensis (Research, Society and Development, 2023)
Medicinal plants Equisetum arvense and Camellia sinensis are popularly used in Brazil to treat obesity and diabetes mellitus. To prove the efficacy and safety of its continuous consumption, this study aimed to evaluate whether these plants could induce weight loss, reduction in body mass index and abdominal circumference, decrease in glycemic indexes, and if they could cause liver and kidney toxicity in research participants. For this purpose, applied longitudinal laboratory research was carried out in a sample of 09 healthy adult individuals who consumed daily, for 28 days, manipulated capsules containing the dry extract of each medicinal plant or capsules containing a placebo. Before, during, and after the experimental phase, the anthropometric variables were measured, and the participant's blood was collected for laboratory tests. Therefore, it could be verified that there was no correlation between the consumption of both plants and the occurrence of significant reduction (p < 0.05) in the sample's weight, body mass index, or abdominal circumference during the clinical trial. However, it was observed that the plant Camellia sinensis showed a hypoglycemic effect in its experimental group. In addition, it was found that none of the plants caused changes in the participant's liver and kidney functions, demonstrating the absence of toxicological effects in the tests. The results confirmed the importance of complementary studies that evaluate the therapeutic potential of the medicinal plants used empirically by the Brazilian population to treat different pathologies, predominantly obesity, and diabetes mellitus.